2022
DOI: 10.7717/peerj.12540
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of green synthesized silver nanoparticles with poly(ethylene glycol) methacrylate and their biomedical applications

Abstract: In the present research, a rapid, simple and efficient green method is used for the incorporation of silver nanoparticles (AgNPs) into poly(ethylene glycol) methacrylate (PEGMA) to create biocatalysts with excellent properties for pharmaceutical purpose. In the first phase, Caralluma tuberculata capped AgNPs (Ca-AgNPs) were prepared using green synthetic approach and in the second phase Caralluma tuberculata capped AgNPs were hybridized with poly(ethylene glycol) methacrylate to form PEGMA-AgNPs. Both the virg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…A recent study has reported the effect of Ct capped AgNPs and Ct capped AgNPs hybridized with poly(ethylene glycol) methacrylate against prostatic adenocarcinoma (PC-3) cell lines. The results confirmed the significant anticancer potential (IC 50 =38 µg/ml and 34 µg/ml respectively) of Ct capped metallic nanoparticles [51]. Other species of Caralluma such as Caralluma acutangula have also been reported for their excellent cytotoxic and anticancer activity against hepatocellular carcinoma (HEPG2) and breast cancer (MCF-7) cells [52].…”
Section: Figure 8) Cellular Uptake and Cytotoxicity Study Of Rhodamin...supporting
confidence: 65%
“…A recent study has reported the effect of Ct capped AgNPs and Ct capped AgNPs hybridized with poly(ethylene glycol) methacrylate against prostatic adenocarcinoma (PC-3) cell lines. The results confirmed the significant anticancer potential (IC 50 =38 µg/ml and 34 µg/ml respectively) of Ct capped metallic nanoparticles [51]. Other species of Caralluma such as Caralluma acutangula have also been reported for their excellent cytotoxic and anticancer activity against hepatocellular carcinoma (HEPG2) and breast cancer (MCF-7) cells [52].…”
Section: Figure 8) Cellular Uptake and Cytotoxicity Study Of Rhodamin...supporting
confidence: 65%
“…Chitosan/poly (vinyl alcohol) blend doped with AgNPs showed an IC 50% of 23.1 μ g/ml against PC-3 cell lines, which is also higher than that obtained from the prepared AgNPs-PVP [ 16 ]. A recent study performed by Anwar et al demonstrated IC 50% values of 38 and 34 μ g/ml for Caralluma tuberculata capped AgNPs and Caralluma tuberculata capped AgNPs hybridized with poly(ethylene glycol) methacrylate, respectively using PC-3 cell lines [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Excessive amounts of ROS can cause a cellular imbalance in the reduction–oxidation reactions and disrupt normal biological functions, leading to oxidative stress, which generates cell damage due to the oxidation of molecules, mutagenesis, cell death, inflammation, and carcinogenesis . α-Lipoic acid is a thiol antioxidant, the precursor of glutathione (GSH), vitamin C, and E. In the reduced form it can react with free radicals; therefore, it can regulate the inflammatory response. , Moreover, PEGMA due to its CC double bond can also contribute to the radical scavenging properties of our aerogels. , To determine the antioxidant capacity of our aerogels, they were placed in contact with the ABTS •+ solution, and the ability to inhibit the oxidation of the radical was measured, at 734 nm . The antioxidant activity was expressed as Trolox equivalent antioxidant capacity (TEAC), determined by using as reference Trolox, a synthetic analog of vitamin E (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“… 53 , 54 Moreover, PEGMA due to its C=C double bond can also contribute to the radical scavenging properties of our aerogels. 55 , 56 To determine the antioxidant capacity of our aerogels, they were placed in contact with the ABTS •+ solution, and the ability to inhibit the oxidation of the radical was measured, at 734 nm. 35 The antioxidant activity was expressed as Trolox equivalent antioxidant capacity (TEAC), determined by using as reference Trolox, a synthetic analog of vitamin E ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%